Epstein-Barr Virus and Human Herpesvirus 8 in Idiopathic Pulmonary Fibrosis - Amir Hossein Jafarian; Nema Mohammadian Roshan; Hossein Ayatollahi; Abbas Ali Omidi; Masoumeh Ghaznavi; Masoumeh Gharib (Iranian Society of Pathology, 2020)
Background & Objective:Idiopathic pulmonary fibrosis (IPF) is a chronic and uniformly fatal interstitial lung disease with incompletely understood pathogenesis. Several studies have given the evidence for and against viral cofactors in the pathogenesis of Idiopathic pulmonary fibrosis. In this study Epstein-Bar Virus (EBV) and Human Herpesvirus 8 (HHV-8) have been studied for a possible role in the pathogenesis of IPF.Methods:Polymerase chain reaction (PCR) was employed for the detection of EBV and HHV-8 in 58 formalin-fixed paraffin-embedded lung tissue specimens (29 controls and 29 IPF specimens).Results:EBV DNA was present in the lung tissue of 6 out of 29 (20.7%) IPF specimens compared with 1 out of 29 (3.4%) controls (P=0.102). The HHV-8 gene was identified in 3 out of 29 (10.3%) cases of IPF specimens. The control group showed no evidence of HHV-8 gene (P=0.227).Conclusion:Although multiple studies are strongly suggestive of a role for EBV and HHV-8 in the development of IPF, there was no statistically significant difference in the prevalence of EBV and HHV-8 DNA in the IPF specimens and controls in this study.